Penerapan PSAK Syariah No. 112 Atas Pengelolaan Waqaf Uang Pada Koperasi Syariah - Eny Latifah; Mitha Fahni Sahira; Nadiyatur Rohmah; Hendrik Setiawan (Inovatif: Jurnal Ekonomi, Manajemen, Akuntansi, Bisnis Digital dan Kewirausahaan, 2022)
The purpose of this study was to determine the management of cash waqf in KSPPS BMT Mandiri Sejahtera Blimbing complies with PSAK 112. This research method is qualitative, descriptive by using triangulation data analysis by combining documentation, observation and interview instruments. This research was conducted at KSPPS BMT Mandiri Sejahtera Blimbing. KSPPS BMT Mandiri Sejahtera is a non-bank Islamic financial institution in the form of a cooperative that combines two financial institutions, namely Baitul Maal and Baitul Tamwil. The results showed that the management of cash waqf was managed based on the benefits and in accordance with the value of the benefits of the waqf assets. One of the forms of cash waqf management carried out at KSPPS BMT Mandiri Sejahtera Blimbing is the form of BMT customers who have waqf awareness.